Perception Operation in Shakespeare's Julius Caesar - TURGUT, Fehmi (Journal of History Culture and Art Research, 2015)
Perception Operation in Shakespeare's Julius Caesar Abstract Contemporary Shakespeare studies have gained a new perspective and created an unprecedented synergy in dramatic criticism with the introduction of Cultural Materialism and New Historicism as critical theories. Within the contexts set by New Historicism and Cultural Materialism, Shakespeare's plays, through polyphonic discourses and dialogues, create environments constructed in the relationships of his characters with one another and with the society on the basis of political and ideological considerations. In Shakespeare's theatrical environments, his characters play their political and ideological roles in a way similar to what happens in the real world politics. In such political and ideological environments, analysing polyphonic discourses and dialogues, critical readers can come up with some political and ideological concepts to analyse and explain the ways things happen and the reasons for why they happen. This study argues that one of these concepts is perception operation/management which Shakespeare uses in Julius Caesar as a means of political and ideological propaganda in the same way as is used in the contemporary real world, which creates a close association between the play's original context and contemporary political context through contemporary interpretations. Hence, this study deals with the role of perception operation/management in Brutus' manipulating attempts at political resistance to Julius Caesar's ruling, which paved the way for Caesar's assassination.